Efektivitas Ekstrak Syzygium Polyanthum Sebagai Terapi Dislipidemia - Rizca Yunanda (ANATOMICA MEDICAL JOURNAL | AMJ, 2020)
Dyslipidemia is a lipid metabolic disorder characterized by increased total cholesterol, Low-Density Lipoprotein (LDL) cholesterol, triglycerides (TG), or elevated levels of High-Density Lipoprotein (HDL) cholesterol. Dyslipidemia is one of the main factors that caused atherosclerosis by coronary heart disease (CHD), stroke, and peripheral vascular disease that is incorporated in cardiovascular disease (PKV). Factors that cause dyslipidemia in Indonesia are people who need foods low in fiber and high fat. Mortality from the World Health Organization (WHO) in 2008 obtained 17.3 million deaths in the world caused by cardiovascular disease and will increase to reach 23.3 million deaths by 2030. Traditional therapy is still one option that is still being taken into account in Indonesia. The use of herbal therapy as a therapy for dyslipidemia can be one way out with the use of Syzygium polyanthum or often known as bay leaf. From several studies reported, bay leaf extract has Substance Flavonoids, Tannins, Saponins and Vitamins C, B3, A, and E which in some studies have been linked to studies of fat in the body. Based on this, bay leaf can be a potential alternative for the development of dyslipidemia to reduce mortality from cardiovascular disease.Keywords: dyslipidemia, lipids, Syzygium polyanthum